Role of prior and peri-excisional Human Papillomavirus Vaccination, including the 9-Valent vaccine, on subsequent lower genital tract dysplasia following cervical excisional surgery: A Systematic review. - Palanivelu, Dr.Suvarna; Shunmugavelu , Dr.Karthik (Student's Journal of Health Research Africa, 2024)
Background Cervical excisional procedures, such as the loop electrosurgical excision procedure and conization, are standard treatments for high-grade cervical intraepithelial neoplasia. Despite effective lesion removal, recurrence or persistence of lower genital tract dysplasia remains a clinically relevant concern. Prophylactic human papillomavirus vaccination, particularly the 9-valent vaccine, has been proposed as a secondary preventive strategy to reduce post-treatment disease recurrence. Objective: To systematically evaluate the effect of human papillomavirus vaccination administered prior to or around the time of cervical excisional surgery, with emphasis on the 9-valent vaccine, on subsequent lower genital tract dysplasia. Methods This systematic review followed PRISMA 2020 guidelines. A comprehensive search was conducted across PubMed/MEDLINE, Embase, Scopus, Web of Science, and Google Scholar. Comparative studies evaluating vaccinated versus unvaccinated women undergoing cervical excisional treatment and reporting post-treatment dysplasia outcomes were included. Owing to heterogeneity in vaccine type, vaccination timing, and outcome definitions, a qualitative narrative synthesis was performed. Results Seven studies met the inclusion criteria, including post-hoc analyses of randomized trials and observational cohort studies. One study specifically evaluated prior 9-valent human papillomavirus vaccination, while the remaining studies assessed quadrivalent or mixed vaccine schedules administered before or after excisional treatment. Across all studies, vaccinated women consistently demonstrated lower rates of recurrent cervical intraepithelial neoplasia grade 2 or higher, high-grade squamous intraepithelial lesions, or lower genital tract dysplasia compared with unvaccinated controls. Conclusion Current evidence indicates that human papillomavirus vaccination administered prior to or around cervical excisional surgery is associated with a reduced risk of subsequent lower genital tract dysplasia. While most data support peri- or post-excisional vaccination, emerging evidence suggests additional benefit with prior 9-valent vaccination. Future research Prospective randomized trials and large population-based cohort studies are needed to clarify optimal vaccination timing, compare vaccine valencies, and standardize post-treatment outcome assessment.